Cournot Equilibrium with Free Entry - Novshek, William (Review of Economic Studies, 1980)
Journal Article Cournot Equilibrium with Free Entry Get access William Novshek William Novshek Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 3, April 1980, Pages 473–486, https://doi.org/10.2307/2297299 Published: 01 April 1980 Article history Received: 01 October 1977 Accepted: 01 May 1979 Published: 01 April 1980